Identification and Investigation of Autolysin Genes in Clostridium saccharoperbutylacetonicum Strain N1-4 for Enhanced Biobutanol Production - Jiménez-Bonilla, Pablo (2021)
Biobutanol is a valuable biochemical and one of the most promising biofuels. Clostridium saccharoperbutylacetonicum N1-4 is a hyperbutanol-producing strain. However, its strong autolytic behavior leads to poor cell stability, especially during continuous fermentation, thus limiting the applicability of the strain for longterm and industrial-scale processes. In this study, we aimed to evaluate the role of autolysin genes within the C. saccharoperbutylacetonicum genome related to cell autolysis and further develop more stable strains for enhanced butanol production. First, putative autolysin-encoding genes were identified in the strain based on comparison of amino acid sequence with homologous genes in other strains. Then, by overexpressing all these putative autolysin genes individually and characterizing the corresponding recombinant strains, four key genes were pinpointed to be responsible for significant cell autolysis activities. Further, these key genes were deleted using CRISPR-Cas9. Fermentation characterization demonstrated enhanced performance of the resultant mutants. Results from this study reveal valuable insights concerning the role of autolysins for cell stability and solvent production, and they provide an essential reference for developing robust strains for enhanced biofuel and biochemical production.